Cytotoxic Effect of Ethanolic Extract Fractions of Indonesia Plant Ficus septica Burm. F. on Human Breast Cancer T47D cell lines - Agung Endro Nugroho; Muthi Ikawati; Adam Hermawan; Dyaningtyas Dewi Pamungkas Putri; Edy Meiyanto (International Journal of Phytomedicine, 2011)
Ficus septica Burm. F. (Moraceae) is a plant which grows widely in some areas of Indonesia and other Southeast Asia countries. Previously, ethanolic extract of the plant leaves exhibit cytotoxic effect on several cell lines including T47D cells. The extract also showed chemoprevention effect in vivo. In the study, the ethanolic extract was fractionated gradually by n-hexane and ethyl acetate to yield four fractions including n-hexane soluble fraction, n-hexane insoluble fraction, ethyl acetate soluble fraction and ethyl acetate insoluble fraction. These fractions were then investigated for their cytotoxic effect on T47D cells. The cell viability were assessed using MTT colorimetric assay. The results showed that the cytotoxic effect of nhexane insoluble fraction (IC50 : 9.3 µg/mL) was much more potent than this of n-hexane soluble fraction (IC50 : 331.0 µg/mL). Hexane insoluble fraction was then fractionated with ethyl acetate to provide ethyl acetate soluble fraction and ethyl acetate insoluble fraction. The cytotoxic effect of ethyl acetate soluble fraction (IC50 : 13.7 µg/mL) was much more potent than this of ethyl acetate insoluble fraction (IC50: >700 µg/mL). In conclusion, n-hexane insoluble fraction and ethyl acetate soluble fraction exhibited potent cytotoxic on breasr cancer T47D cell lines. The fractions are potential to be developed as anticancer agent in breast cancer therapy.